DETERMINATION of SILICON IN LUBRICANT OIL BY HIGH-RESOLUTION CONTINUUM SOURCE FLAME ATOMIC ABSORPTION SPECTROMETRY USING LEAST-SQUARE BACKGROUND CORRECTION and INTERNAL STANDARDIZATION - Raposo, Jorge Luiz [UNESP]; Oliveira, Silvana Ruella [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nobrega, Joaquim Araujo; Jones, Bradley Todd (Taylor & Francis Inc, 2011)
The least-squares background correction (LSBC) and internal standardization procedures were combined to eliminate spectral interferences caused by the CS molecular band (251.602 nm) and transport effects for determining Si in sulfuric acid digests of lubricant oil by high-resolution continuum source flame atomic absorption spectrometry. Aluminum, Ba, Ti, V, and W were tested as internal standard (IS) candidates, and W provided the best results. For absorbance measurements of solutions containing 0.5-5.0 mg L-1 Si in the presence of 25 mg L-1 W (at the wavelength integrated absorbance equivalent to 3 pixels), the correlation coefficient for the ratio of absorbance of Si to absorbance of W vs. analyte concentration was 0.9978. Fluctuations in analytical signals due to variations in sulfuric acid concentrations or acetylene/nitrous oxide flow-rate ratios were corrected by using this calibration plot. Relative standard deviations varied from 1.9 to 7.2% and 2.1 to 5.4% (n=12) with and without LSBC/IS, respectively. Recoveries for samples spiked with 2.0 mg L-1 Si in 5.0% (v/v) sulfuric acid were within the 72.5-82.5% and 94.0-99.0% ranges without correction and by LSBC associated with internal standardization procedure, respectively. Accuracy of the proposed method was checked for the determination of Si in commercial lubricant oils and results obtained with internal standardization were better than those without correction.
Keywords: High-resolution continuum source atomic absorption spectrometry; Internal standardization; Lubricant oil; Silicon